Case Study of Nephritis in Domestic Cats (Felis Catus) Male in Veterinary Teaching Clinic of Hasanuddin University - Waode Santa Monica; Indah Windy Octaviyani; Musdalifah Musdalifah (Hasanuddin University, 2019)
ABSTRACT: A pet such as a domestic cat (Felis Catus) with a sterile male sex aged 1 year 7 months with a body weight of 3.7 kg where the animal is affected by urinary system disorders namely Nephritis. Nephritis is kidney inflammation that can occur in the glomerulus, pyelum or tubules. Clinical symptoms shown in patients include polyuria, decreased appetite, and vomiting. For the diagnosis of Nephritis clinically evaluated based on changes in urination behavior, palpation of the dorsal abdominal caudal thoracic is temporarily labored based on a urine dipstick test containing protein ++ (± 100 mg / dL), leukocytes valued at +, urine specific gravity of 1,015 while based on ultrasound examination thickening of the renal cortex, medullary and cortical border is not apparent, renal size is 4.21 cm, kidney capsules that appear hyperechoic, and ascites in the abdomen. Cats treated with isotonic fluid infusion fluids, wet and dry diet diets, antibiotics, multivitamins, and anti-inflammatory. Inpatient animals for 4 days showed improvement in clinical symptoms, namely drinking quite well, starting to stand up, there was movement for activities, and urine was clearer.